Identifying groundwater degradation sources in a Mediterranean coastal area experiencing significant multi-origin stresses - Boumaiza, Lamine; Chesnaux, Romain; Drias, Tarek; Walter, Julien; Huneau, Frédéric; Garel, Emilie; Knoeller, Kay; Stumpp, Christine (Science of The Total Environment, 2020)
This study investigates the multiple contamination sources of a coastal Mediterranean aquifer in northeastern Algeria that is bordered by two rivers and neighboring densely populated areas. Hydrogeochemical and isotopic groundwater characterization is carried out, including the analyses of major elements, water stable isotopes δ2H-H2O and δ18O-H2O, and stable isotopes of nitrate δ15N-NO3 and δ18O-NO3, and then integrated into the history of land use over the study area. Groundwater nitrate concentrations ranging from 1.6 to 235 mg/L with a median value of 69 mg/L are evidence of the degradation of groundwater quality induced by anthropogenic sources. The combined of δ15N-NO3 and δ18O-NO3 ratios showed that nitrate in groundwater is attributable to (i) the uncontrolled development of inadequate private sanitation systems over the study area, and (ii) the unsafe application of animal manure to fertilize crops. Very active saltwater intrusion is confirmed by several hydrogeochemical indicators. Interestingly, the intrusion mechanism appears to be more complex than a direct intrusion from the Mediterranean Sea. During the high-water period, saltwater intrusion may also originate from the two rivers bordering the aquifer, via upstream migration of seawater through the river mouths. The heavier ratios in δ2H-H2O and δ18O-H2O of surface water collected from the rivers suggest that water from the Mediterranean Sea is mixing with water in the rivers. Multi-source contamination not only contributes to complex chemical reactions within the aquifer, but also contributes, via the cumulative effect of the various sources, to affecting large parts of the study area. The present study may serve as a warning to the effect that historical land-use practices may exert seriously deleterious impacts on groundwater quality and greatly limit conditions for the sustainable management of Mediterranean coastal areas.